Isotopic Proveniencing and Mobility
VIII, 273 p. 1 illus.
Keywords: This volume provides a state-of-the-art presentation and discussion of procedures, especially what works and what doesn’t — on isotopic proveniencing, learned over the last 30 years. The volume focuses on application, not method, to emphasize to the reader the wide range of questions that can be addressed using isotopic proveniencing. Topics covered include samples, baselines, isoscapes, and place of origin. Isotopic proveniencing has become almost standard procedure in the analysis of archaeological burials as a means of distinguishing locals from foreigners. The combination of isotopic proveniencing and DNA has moved archaeological interest in migration and mobility to the fore, but there is very little synthetic work published for either technology.The field has evolved and new procedures and guidelines have emerged that have not been widely heard and this volume seeks to rectify this. The contributors have been selected from among the leaders in the field, those withactive research and hands-on experience with the technology. This volume is of relevance to archaeologists.